Picosecond/THz acoustic measurements of semiconductor devices - Devireddy, Srikanth Reddy (2018)
This thesis investigates the electron-phonon interactions in fabricated Semiconductor Devices i.e. Schottky Diodes, Quantum Well (QW) embedded p-i-n photodiodes, two dimensional electron gas (2DEG) and two-dimensional hole gas (2DHG) structures all on (311) GaAs substrates. Fast electrical measurements were performed on Schottky diodes fabricated on the (311B) GaAs surface. Optical excitation generates a compressive strain pulse in an Al film which is at the opposite side of the GaAs substrate. Two coherent acoustic phonon modes were generated in the (311B) GaAs substrate: quasi-longitudinal phonons (QLA) and quasi-transverse phonons (QTA). These two modes were detected successfully using the Schottky diode, the dependence of QLA and QTA signals on different applied bias, pump powers and temperatures were investigated.